(untitled) - Krauss, Gerhard (Chichester, 2001)
Over the last decade there has been great progress in the understanding of the molecular basis of signal transduction, and many facts are now basic knowledge for every medicinal chemist, biochemist, and biologist. Since an integral description of cellular regulation and signal transduction is scarcely covered in textbooks, this book fills a real gap. Starting from the principles of gene regulation and regulation of enzyme activity, the topics of this book cover function, structure, and integral construction of signalling pathways plus a detailed description of the various types of carriers such as second messengers, protein kinases, and transmembrane receptors. Central cellular processes like cell cycle regulation, oncogenesis and apoptosis are discussed in light of the properties of the signalling molecules involved. With didactic skill and clarity the author relates the observed biological phenomena to the underlying biochemical processes.
Keywords: Cellular signal transduction,Tế bào truyền tín hiệu